Artificial intelligence. Creation of an artificial neural network - Fesenko, O (My University, 2019)
Artificial intelligence technologies are used in tasks that are beyond human capabilities. The main problem of the topic of artificial intelligence is not the willingness and lack of confidence of most people in such technologies, but still no one is fully aware of how artificial intelligence works - this is the fact, that cannot be challenged so the purpose of the article is to describe and explain the main paradigms of the artificial intelligence functioning, on the example of neural networks.
Keywords: Neural network; Artificial intelligence; Technologies; Impulse